2017
DOI: 10.1155/2017/8036535
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Interventions for Nutritional Assessment among Pregnant Mothers in Northeastern Uganda

Abstract: Introduction Assessment of pregnant mothers for nutritional status is a neglected intervention. In Kaabong Hospital, nutritional status of pregnant mothers was not assessed during antenatal care (ANC) visits. A quality improvement (QI) project was initiated to increase nutritional assessment using midupper arm circumference (MUAC) among pregnant mothers during ANC visits from 0 to 90% between April and September 2015. Method Baylor-Uganda formed ANC Work Improvement Team (WIT) that reviewed ANC register, ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As CQI is a deliberate effort in addressing low performance, it is not surprising that rates of treatment success improved. Although publications on use of CQI in TB control programs are scarce despite existence of TB specific CQI framework [18], in HIV programs, the use of CQI has remarkably improved early infant HIV diagnosis at 6 weeks [27], nutritional assessment among pregnant mothers [28], and retention of HIV positive adolescents in care [29]. Overall, it is important to recognize that certain districts have CQI teams while others do not.…”
Section: Discussionmentioning
confidence: 99%
“…As CQI is a deliberate effort in addressing low performance, it is not surprising that rates of treatment success improved. Although publications on use of CQI in TB control programs are scarce despite existence of TB specific CQI framework [18], in HIV programs, the use of CQI has remarkably improved early infant HIV diagnosis at 6 weeks [27], nutritional assessment among pregnant mothers [28], and retention of HIV positive adolescents in care [29]. Overall, it is important to recognize that certain districts have CQI teams while others do not.…”
Section: Discussionmentioning
confidence: 99%
“…As CQI is a deliberate effort in addressing low performance, it is not surprising that rates of treatment success improved. Although publications on use of CQI in TB programs are scarce despite existence of TB specific CQI framework,(16) in HIV programs, the use of CQI has remarkably improved early infant HIV diagnosis at six weeks, (25) nutritional assessment among pregnant mothers, (26) and retention of HIV positive adolescents in care. (27) This study found that districts with high rates of treatment success commonly used Village Health We found lack of motivated and dedicated TB focal persons influenced low rates of treatment success which is in agreement with a former study where low staff motivation undermined the provision of good quality TB services in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare the success of our study to others because of the limited amount of trials of this nature. A Ugandan study showed an improvement from 0% to 79% in a 2‐month span for nutritional screenings of pregnant mothers . Again, there are few studies to compare an intervention like ours to any other, but some studies have attempted to improve calorie and protein intake in inpatient groups with varying amounts of success …”
Section: Discussionmentioning
confidence: 98%
“…A Ugandan study showed an improvement from 0% to 79% in a 2-month span for nutritional screenings of pregnant mothers. (25) Again, there are few studies to compare an intervention like ours to any other, but some studies have attempted to improve calorie and protein intake in inpatient groups with varying amounts of success. (26,27) Our study is limited by the scope of the patient population and by not having measurable caloric and protein consumption of patients.…”
Section: Original Article | 1797mentioning
confidence: 99%